Análise da competitividade do cluster da bovinocultura de corte em Santana do Livramento- RS e Rivera - UY - Villamour, Débora Adriane Bonadiman (2021)
The present study aims to analyze the competitiveness of the beef cattle cluster in Santana do Livramento - RS and Rivera - UY. Analyzing the eleven elements of competitiveness of a cluster, verifying which factors can represent them and identifying the aspects that can be improved in the cluster's competitiveness. The research has a descriptive character with a qualitative approach, with a case study method. Data collection was carried out through the websites of research institutes, organizations, scientific articles and semi-structured interviews. For the data analysis technique, content analysis was used, which was divided into three sessions. The results showed that most of the competitiveness fundamentals are present in the beef cattle cluster, it is also possible to identify the possible aspects of improvements so that it is more competitive.